Rural-urban migration as a factor associated with physical and sexual intimate partner violence Peru 2015-2017: a secondary analysis of a national study - Jorge Terrazas; Dora Blitchtein (BMC, 2022)
Abstract Background Internal migration, a consequence of the demographic transition towards urbanization driven by globalization, represents a particular public health challenge. Change in residence from one sociocultural geographic context to another, with not only economic implications, but also changes in women's long-established relationships of family interdependence, influences gender relations and can influence Intimate Partner Violence (IPV) against women. Different migratory trajectories may be related to IPV. The aim of this study was to identify the association between internal migration and physical and/or sexual violence against women in the last 12 months. Methods A secondary analytical cross-sectional analysis of the publicly accessible 2015-2017 Demographic and Family Health Survey (DHS) was performed. The outcome variable was reported physical and/or sexual violence inflicted by the partner (IPV) during the last 12 months. Exposure variable was internal migration, operationalized from three questions: current place of residence, principal place of residence before 12 years of age and number of years of residence in the current place. Migrants were classified as those who reported having lived for 5 years or more in the current location and were categorized as rural-rural migrants, urban-urban migrants, urban-rural migrants and rural-urban migrants, recent migrants and nonmigrants those who resided in the same place all their lives. To identify the association between internal migration and physical violence, a generalized linear model (GLM) of the family and the log Poisson link log option was used, and the results are presented as prevalence ratios (PRs). A crude model and a model adjusted for confounding variables were performed. Results Rural-urban migrant women had a 15.0% higher probability of experiencing IPV than nonmigrant women (PRa 1.15, 95% CI 1.03-1.29, p = 0.015), while the probability of experiencing IPV in the last 12 months for urban-rural, rural-rural,urban-urban migrantand recent migrant women was not significantly different from that of nonmigrant women. Conclusion Rural-urban migration among women of childbearing age is a factor associated with a higher probability of IPV in the last 12 months. The identification of women with this rural-urban migration pattern could help prioritize those that may experience a greater probability of physical and/or sexual violence in Peru, it must be studied if this pattern is the same in other countries.